My mini book of alphabet (Say Publishing Karachi, 2011)
This captivating mini book introduces young learners to the building blocks of language: the alphabet. Through colorful illustrations and simple words, children will learn to recognize and sound out each letter. Each page features a different letter, accompanied by a word that begins with that letter. This engaging book aims to stimulate language development, phonics skills, and a love of reading.